Conteúdos do ensino em contabilidade forense: percepção de especialistas em fraudes - Leonardo Barbosa Amaral (2019)
The teaching of Forensic Accounting has been a recurring theme in international literature and not without controversy. This study reports fraud specialists perceptions about the teaching of Forensic Accounting, more specifically, it seeks to identify the contents that must be addressed in order to develop the knowledge and skills inherent to Forensic Accounting, using the Delphi technique. For this purpose, a commission comprising 25 Brazilian specialists was assembled, with heterogeneous training, represented both by academic and professional fields. Based on literature review, initially, 34 contents were submitted to the commission, one of which was excluded after the first round. Furthermore, the experts added 14 new contents and several comments were made throughout the process. Three rounds were required to reach consensus. The results of the study indicate that the experts perceive that most of the contents proposed by the international literature are relevant, and that the Delphi technique evidenced the ranking of the most important ones. Among the best-ranked contents, the majority are those related to the examination of fraud and corruption, including contents such as: Prevention, Detection and Fraud Investigation, Investigation Techniques (Bribery and Corruption), Study of Money Laundering Cases and Other Frauds, Definition of Fraud, Types of Fraud, Money Laundering Prevention, Hidden Asset Localization Techniques, and Fraud Triangle. The results of the partitioned sample (academics versus practitioners) revealed that there were not only differences in the ranking of contents, but also some statistically significant differences in perceptions between the two groups using the Chisquare test (²) and the Mann-Whitney test. Practitioners tend to rank fraud-related content higher than academics, perhaps motivated by their professional experiences. Even though there is no consensus in literature on the educational level for forensic accounting education, the panel of experts understands that it should be in a specialization level. This study advances in the literature on the teaching of Forensic Accounting and its results provide useful insights into this recurring research topic. This work can be especially handy for contractors, students, and universities, or anyone who has never heard of Forensic Accounting.